Telehealth Utilization in Response to the Novel Coronavirus (COVID-19) Pandemic in Orthopaedic Surgery. Issue 11 (1st June 2020) - Parisien, Robert L.; Shin, Max; Constant, Michael; Saltzman, Bryan M.; Li, Xinning; Levine, William N.; Trofa, David P.
Abstract : Introduction: The purpose of this investigation is to assess the current utilization of telehealth capabilities at academic orthopaedic departments in the United States and to determine how practice patterns have been directly influenced by the coronavirus disease 19 (COVID-19) pandemic. Methods: Orthopaedic surgery programs participating in the Electronic Residency Application Service were identified. One hundred seventy-five (175) programs were presented with a seven-item questionnaire addressing whether each program is using telehealth services in response to the COVID-19 pandemic. Results: Of the 175 Electronic Residency Application Service participant orthopaedic programs, 168 responded for a total response rate of 96%. Of the 106 institutions using telehealth services, 88 (83%) cited the COVID-19 pandemic as the impetus for implementation of telehealth services. Institutions located in the Northeast and South regions were markedly more likely to offer telehealth services. Heat map analysis demonstrates an associative overlap of regional "hot spots" with direct comparison of COVID-19 cases in the United States and orthopaedic departments providing telehealth services. Discussion: This study demonstrates the impressive measures academic orthopaedic institutions are taking to meet the needs of our patients by identifying a notable increase in new telehealth offerings throughout the United States with a positive correlation with COVID-19 disease burden.